GUIDANCE SERVICES FOR LEARNERS WITH SPECIAL EDUCATIONAL NEEDS: PERSPECTIVE OF JHS TEACHERS AND COUNSELLORS IN BIRIM CENTRAL MUNICIPALITY, GHANA - Philemon Amaniampong; Judith Amankwaa Mensah; Eleanor Bosompemaa Takyi, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The purpose of the study was to explore guidance services provided for learners with special needs in selected Junior High Schools in Birim Central Municipality. The study adopted the descriptive survey design. The purposive sampling technique was used to select counsellors while the simple random technique was used for teachers with a sample size of 61. The questionnaire was used to collect the data. The study revealed that teachers have limited knowledge in guidance and counseling and few teachers also counsel learners with special needs even though they were not counselors. Again, it also revealed that appraisal, information, consultation, counseling, and orientation were guidance services provided to learners with special needs but the most common guidance services provided by teachers and counselors to learners with special needs were consultation service, 30(49.2%), and counselling service, 25(40.1%). It was recommended that the Municipal guidance and counseling coordinator should collaborate with the special education coordinator and the teachers to organise series of workshops on guidance services for teachers to update their knowledge on counseling.